On behaviour of integral curves in the vicinities of optimal integral varieties - Kurbanshoev , S. Z. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We describe an explicit construction of optimal integral manifolds [1] for a quasilinear system of differential equations that uses the method of successive approximations. We study the behavior of integral curves in the neighborhood of optimal integral manifolds. We cite a numerical method of synthesis of optimal control and prove its justification.